Prevalence of Thyroglobulin Antibody (TgAb) positivity in patients post treatment for differentiated thyroid carcinoma and verification of serum thyroglobulin measurements by thyroglobulin recovery test and TgAb assay - Kathiravelu, Kaameny; Samsudin, Intan Nureslyna; Mat Salleh, Mohd Jamsani; Thambiah, Subashini C. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Thyroglobulin (Tg) measurement is important for detection of disease recurrence in patients with differentiated thyroid carcinoma (DTC). However, its measurement is affected by Tg autoantibodies (TgAb). Cal- culation of Tg recovery may complement quantitative TgAb measurement in detection of interference. This study aimed to determine the prevalence of TgAb positivity in Tg samples received from post-thyroidectomy DTC patients in Hospital Pulau Pinang (HPP). Additionally, we assessed the use of the Tg II Confirmatory Test (Roche Diagnostics) assay to calculate Tg recovery in detecting Tg assay interference. Method: Samples received for Tg measurements from post-thyroidectomy DTC patients with TgAb positivity were tested with Tg II Confirmatory Test. The Tg levels [categorised as biochemically detectable (1.0 μg/l) vs biochemically undetectable (<1.0 μg/l)], TgAb and Tg recov- ery [categorised as correct (70%-130%) vs compromised (<70% and >130%) recovery] were interpreted with the diagnostic radioiodine uptake (RAI) results. Results: In this study, 58/73 (79.5%) samples with TgAb positivity had undetectable Tg. A compromised Tg recovery was observed in three (4.1%) samples. Only 51 out of 73 subjects had an RAI performed, out of which 27 (52.9%) had increased RAI uptake (radiological evidence of persistent/recurrent disease). Of those with increased RAI uptake, 17 (63%) had biochemically undetectable Tg, out of which none had compromised Tg recovery. Conclusion: The presence of TgAb prevents reliable measurement of Tg. The Tg II Con- firmatory assay for calculation of Tg recovery did not provide additional complementary value to quantitative TgAb measurement in the detection of interference in Tg measurements.